Privacy vulnerabilities and data security challenges in the IoT - Agarwal, Shivani; Makkar, Sandhya; Tran, Duc-Tan (Boca Raton, FL : CRC Press, 2021)
"This book discusses the evolution of security and privacy issues in the Internet of Things. The book focuses on bringing all security and privacy related technologies into one single source so that students, researchers, academicians, and those in the industry can easily understand the IoT security and privacy issues. This edited book uses Security Engineering and Privacy-by-Design principles to design a secure IoT ecosystem and to implement cyber-security solutions. This book takes the readers on a journey that begins with understanding the security issues in IoT-enabled technologies and how it can be applied in various aspects. It walks readers through engaging with security challenges and builds a safe infrastructure for IoT devices. The book helps researchers and practitioners understand the security architecture through IoT and the state-of-the-art in IoT countermeasures. It also differentiates security threats in IoT-enabled infrastructure from traditional ad hoc or infrastructural networks, and provides a comprehensive discussion on the security challenges and solutions in RFID, WSNs, in IoT. This book aims to provide the concepts of related technologies and novel findings of the researchers through its chapter organization. The primary audience incorporates specialists, researchers, graduate understudies, designers, experts and engineers who are occupied with research and security related issues"--
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things -- Security measures; TECHNOLOGY / Manufacturing; COMPUTERS / Computer Science; COMPUTERS / Data Processing / General